A closer look at the role of nutrition in children and adults with ADHD and neurodivergence - Hunter, Catherine; Smith, Carla; Davies, Emily; Dyall, Simon C.; Gow, Rachel V. (Frontiers in Nutrition, 2025)
IntroductionThe role of nutrition in Attention-Deficit, Hyperactivity Disorder (ADHD) and other neurodivergent conditions is of growing public and research interest. There is little research reporting vitamin, mineral and omega-3 fatty acid levels in ADHD and brain health.MethodsThis study presents nutritional and psychological data from a community UK sample of children (n = 47, Mean age: 10.1 years) and adults (n = 10, Mean age: 29.8 years) with ADHD, autism, dyslexia and other neurodivergent conditions (total n = 57). The participants undertook a blood draw which measured a range of vitamins, minerals and omega-3 fatty acids as well as food allergies and food intolerances which were then correlated with psychological symptom scores measuring ADHD symptoms.ResultsThe key findings, revealed that both children and adults presented with a range of insufficiencies in key nutrients which facilitate neurotransmitter function and, which are deemed as brain-essential, namely omega-3 fatty acids, zinc, B-vitamins and vitamin D. Furthermore, significant relationships were observed between nutrient levels and ADHD symptom severity in the children’s group. For example, red blood cell magnesium was negatively correlated with the Conners CI-Parent Rating Scale (CPRS) Disruptive Behavior scores (rho = −0.597, p = 0.024). The omega-3 index (sum of EPA + DHA as a percentage of total fatty acids) was negatively correlated with their Learning and Language Disorder scores, (rho = −0.601, p = 0.018). Magnesium levels were also associated with overall ADHD symptom severity (rho = −0.612, p = 0.02), implying that the greater the severity of ADHD symptoms, the lower the magnesium. This clinical cohort also presented with a range of food intolerances with over 80% of participants presenting with high reactivity scores to cow’s milk, other dairy, and casein, and just over half the sample intolerant to wheat and wheat gluten.DiscussionThis is a novel study which presents preliminary data and insights in the role of nutrition in ADHD and neurodivergence. and relationships between nutritional insufficiencies and ADHD-symptoms. It specifically demonstrates a range of food intolerances and relationships between nutritional insufficiencies and ADHD-symptoms, which warrant further exploration in larger case-control groups.